2018
DOI: 10.1080/21645515.2018.1438792
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of different seasonal influenza vaccines in the elderly Italian population

Abstract: ABSRACTIn the perspective of reaching at least 75% influenza vaccination coverage in the elderly and substantial budget constraints, Italian decision makers are facing important challenges in determining an optimal immunization strategy for this growing and particularly vulnerable population. Four different influenza vaccines are currently available for Italian older adults aged 65 years or above, namely trivalent inactivated vaccines (TIVs), MF59-adjuvanted TIV (MF59-TIV), intradermal TIV (ID-TIV) and quadriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 60 publications
3
51
0
2
Order By: Relevance
“…Furthermore, two potentially eligible studies and five conference abstracts were identified through manual search. A total of 18 studies, corresponding to 13 full papers [31][32][33][34][35][36][37][38][39][40][41][42][43] and 5 conference abstracts [44][45][46][47][48] were included in the qualitative assessment. The whole process of study selection is illustrated in Figure 1.…”
Section: Study Selection Processmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, two potentially eligible studies and five conference abstracts were identified through manual search. A total of 18 studies, corresponding to 13 full papers [31][32][33][34][35][36][37][38][39][40][41][42][43] and 5 conference abstracts [44][45][46][47][48] were included in the qualitative assessment. The whole process of study selection is illustrated in Figure 1.…”
Section: Study Selection Processmentioning
confidence: 99%
“…The main characteristics of the included studies are reported in Table 1. Most studies (N = 10) were written in English, 31,32,[34][35][36][37][39][40][41]43 while the remaining two in Spanish 38,42 and one in Italian, 33 respectively. All studies were conducted in high-income countries, namely Italy (N = 5), 32,33,36,41,43 the US (N = 3), 34,37,40 Spain (N = 2), 38,42 Canada (N = 2) 35,39 and France (N = 1).…”
Section: Characteristics Of the Included Studies: Full Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Снижение продолжительности жизни с учетом качества в случае заболевания гриппом составило при расчете 0,0078 QALY, при заболевании пневмонией -0,01041 QALY [9].…”
Section: Introductionunclassified